Perancangan dan Pembuatan Aplikasi Sistem Informasi Akuntansi Atas Siklus Pengeluaran dan Pendapatan untuk UD X - Patricia Tanjaya; Silvia Rostianingsih; Saarce Elsye Hatane (Jurnal Infra, 2016)
Accounting system implemented in UD X still being applied manually by recording debts in the account payable ledger and credits in the account payable ledger with a Microsoft Excel application. The company’s revenues were calculated manually by calculating the customer’s invoices and bills because transactions were not recorded in a journal. Hence, UD X requires a large amount of time to process the financial information. Therefore, an accounting information system is needed to record UD X’s transactions in a journal automatically and to process financial report quickly and precisely.According to the analysis based on UD X’s problems, an application to support the UD X’s business performance must be made. The application would be implemented to process the purchase transactions, sales, returns, purchases, sales returns, work orders, loan and credit payments, and accounting reports generator. The design of the Data Flow Diagram system uses Microsoft Visio, and the ERD uses Power Designer 15. The application will be based on CodeIgniter Framework and MySQL for the database.User Satisfaction towards the application’s overall quality is 100% which means the application has fulfilled and corresponds to the system requirements. This application helps the records process by automate the journal recordings and postings, and also helps to speed up the generation of the company’s profit report.